Role Of Xanthine Oxidase, Lipid Peroxidation And Uric Acid In Patients With Acute Myocardial Infarction - PRAMOD KAMBLE; DHIRAJ J. TRIVEDI; ANIL BARGALE; VIJAY PANDHARE; PRAKASH ZENDE; PRADNYA PADALKAR (International Journal of Pharma and Bio Sciences, 2011)
The aim of our study is to determine the effects of alcohol intake and cigarette smoking on the activity of Xanthine oxidase (XO), Lipid peroxidation (LPO) and Uric acid in patients with Acute Myocardial Infarction (AMI). This study includes 60 patients of AMI [smokers (n=15), non-smokers (n=15), alcoholics (n=15) and non-alcoholics (n=15)] and 30 normal controls. Xanthine oxidase, Lipid peroxidation and Uric acid levels in smokers, nonsmokers, alcoholics, non-alcoholics and controls are (34.6±2.9, 33.8±2.4, 34.6±2.8, 33.9±2.5, 30.3±1.2), (5.45±0.75, 5.34±0.86, 5.07±0.82, 5.71±0.61, 2.39±0.82) and (6.24±0.36, 5.78±0.86, 5.78±0.85, 6.24±0.37, 5.2 ±1.82) respectively. Our result shows that the levels of XO, LPO and uric acid in smokers are elevated than controls. Regarding alcoholics there is no significant difference in the study parameters. Therefore, these results mainly focus towards smoking habit which can be an additional factor to enhance the severity of AMI.